2015
DOI: 10.1515/cclm-2014-0475
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of high-sensitivity cardiac troponin T or troponin I compared to creatine kinase in patients with revascularized acute myocardial infarction

Abstract: Kinetic of hs-cTnT and not cTnI differs from CK. The role of hs-cTnT in prognosis has to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 38 publications
(42 reference statements)
6
48
0
Order By: Relevance
“…Furthermore, since cTnI and cTnT are present in the sarcomeric complex in a molecular ratio of 1:1, these differences between the circulating cTns are probably related to differences in intra- [130] or extra-cellular [131][132][133] catabolism and the peripheral turnover of cTnI and cTnT. A recent study [134] found that circulating levels of cTnT, unlike cTnI, have a diurnal rhythm, thus bearing out the hypothesis that there are some differences in the release from cardiomyocytes and/or peripheral turnover between cTnI and cTnT.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 99%
“…Furthermore, since cTnI and cTnT are present in the sarcomeric complex in a molecular ratio of 1:1, these differences between the circulating cTns are probably related to differences in intra- [130] or extra-cellular [131][132][133] catabolism and the peripheral turnover of cTnI and cTnT. A recent study [134] found that circulating levels of cTnT, unlike cTnI, have a diurnal rhythm, thus bearing out the hypothesis that there are some differences in the release from cardiomyocytes and/or peripheral turnover between cTnI and cTnT.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 99%
“…This was recognized and discussed in our study, as well. As the authors have previously shown in patients with STEMI, all three biomarkers-hs-cTnT, hs-cTnI, and CK-MB-show a 1st peak 10.7 hr to 11.8 hr after reperfusion [4,5]. However, only hs-cTnT, but not hs-cTnI or CK-MB, show a biphasic kinetics with a 2nd peak occurring 76.9 hr after reperfusion [4,5].…”
mentioning
confidence: 58%
“…Second, the authors correctly pointed out to the biphasic kinetics of hs‐cTnT elevation in reperfused patients with STEMI and the fact that only the 1st postprocedural hs‐cTnT peak was analyzed and compared with peak creatine kinase myocardial band (CK‐MB) in our study. This was recognized and discussed in our study, as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note the differences in kinetics of CK‐MB, cTn, and hs‐TnT. In patients with acute MI, while the peak values of CK‐MB and cTn are followed by linear decreases post successful PCI, the levels of hs‐TnT follow a biphasic curve, with a second peak noted at 82h . There have not been studies looking at associations between the two hs‐cTnT peaks and mortality.…”
mentioning
confidence: 99%